Proposed Dashboard Concept for TUS MART: Enhancing Aquaponic and Hydroponic Sales Management Using the Innovation Canvas Method - Putra, Perdana Suteja; Zunaidi, Rizqa Amelia; Hidayati, Sri; Mardhiana, Hawwin; Chandra, Huki; Novika, Norma (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
The rapid evolution of e-commerce has transformed agricultural operations, prompting Telkom University Surabaya to develop TUS MART, an e-commerce platform designed for managing and selling aquaponic and hydroponic products cultivated by the university. However, TUS MART faces challenges such as inadequate data management, limited user interface intuitiveness, and inefficiencies in sales tracking and customer relationship management. This research proposes a comprehensive dashboard for TUS MART, developed using the Innovation Canvas Method, which aligns with both user needs and business objectives. The methodology involved phases like